(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The author’s intention is to offer in this paper an informative historical reading on the conduct of liberalism throughout history, with a brief overview of the doctrine of human rights as its offspring and point out the problems arising from their practical (mis)application by people who consider themselves liberals due to their misunderstanding of ideology’s internal contradictions: plasticity and corrigibility of the primary principles of liberalism and ways to overcome them.